Fatal Attraction? Extended Unemployment Benefits, Labor Force Exits, and Mortality - Andreas Kuhn; Stefan Staubli; Jean-Philippe Wuellrich; Josef Zweimüller (Institute of Labor Economics (IZA), 2018)
We estimate the causal effect of permanent and premature exits from the labor force on mortality. To overcome the problem of negative health selection into early retirement, we exploit a policy change in unemployment insurance rules in Austria that allowed workers in eligible regions to exit the labor force 3 years earlier compared to workers in non-eligible regions. Using administrative data with precise information on mortality and retirement, we find that the policy change induced eligible workers to exit the labor force significantly earlier. Instrumental variable estimation results show that for men retiring one year earlier causes a 6.8% increase in the risk of premature death and 0.2 years reduction in the age at death, but has no significant effect for women.
Keywords: I10; I12; J14; J26; 330; early retirement; mortality; health behavior; instrumental variable